Agent-based Prototyping of Web-based Systems - Krishna, Aneesh; Guan, Y.; Sambattheera, C.; Ghose, A. (Springer-Verlag, 2006)
Agent-oriented conceptual modelling in notations such as the i* framework [13] have gained considerable currency in the recent past. Such notations model organizational context and offer high-level social/ anthropo-morphic abstractions (such as goals, tasks, softgoals and dependencies) as modelling constructs. It has been argued that such notations help answer questions such as what goals exist, how key actors depend on each other and what alternatives must be considered. Our contribution in this paper is to show an approach to executing high-level requirements models represented in the i* agent-oriented conceptual modelling language. We achieve this by translating these models into sets of interacting agents implemented in the 3APL language. This approach enables us to analyze early phase system models by performing rule-/consistency-checking at higher-levels of abstraction. We show how this approach finds special application in the analysis of high-level models of a web-based system.